Usefulness of catheter tip culture in the diagnosis of neonatal infections - Marconi, Camila [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP]; Lyra, João César [UNESP]; Bentlin, Maria Regina [UNESP]; Batalha, Jackson E. N. [UNESP]; Sugizaki, Maria Fatima [UNESP]; Corrente, José Eduardo [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP] (Sociedade Brasileira de Pediatria, 2009)
Objective: To determine the number of colony-forming units (CFU) that best correlates with catheter-related infections (CRI) in newborns.Methods: This was a prospective study of semiquantitative cultures of catheter tips obtained from newborns in the neonatal unit at Faculdade de Medicina de Botucatu, state of São Paulo, Brazil. The microorganisms isolated from catheter and peripheral blood cultures were identified and submitted to a drug susceptibility test. The optimal cutoff point was determined by the receiver operating characteristic (ROC) curve.Results: A total of 85 catheters obtained from 63 newborns were studied. Staphylococcus epidermidis was the predominant species in the catheters (75%). Eight of 11 (72.7%) CRI episodes were associated with coagulase-negative staphylococci, six of which were of the S. epidermidis type. ROC curve analysis indicated that the optimal cutoff point for the diagnosis of CRI was 122 CFU.Conclusions: The cutoff point of 122 CFU correlated best with the diagnosis of CRI in newborns.